Phase inversion-based nanoemulsions of medium chain triglyceride as potential drug delivery system for parenteral applications - Busmann, Eike Folker; Martínez, Dailén García; Lucas, Henrike; Mäder, Karsten (Beilstein Journal of Nanotechnology, 2020)
Lipid nanoemulsions are attractive drug delivery systems for lipophilic drugs. To produce nanoemulsions with droplets of very small diameter (<100 nm), we investigated thermotropic phase transitions as an alternative to the standard procedure of high-pressure homogenization. Employing shock dilution with ice-cold water during the phase inversion gives the opportunity to produce nanoemulsions without any use of potentially toxic organic solvents. The systematic investigation of the relation of the three involved components surfactant, aqueous phase and lipid phase showed that depending on the ratio of surfactant to lipid the emulsions contained particles of diameters between 16 and 175 nm with narrow polydispersity index distributions and uncharged surfaces. Nanoemulsions with particles of 50 and 100 nm in diameter showed very little toxicity to fibroblast cells in vitro. An unusual, exponential-like nonlinear increase in osmolality was observed with increasing concentration of the nonionic surfactant Kolliphor HS 15. The experimental results indicate, that nanoemulsions with particles of small and tunable size can be easily formed without homogenization by thermal cycling.
Keywords: cellular toxicity; isotonicity; nanoemulsion; phase inversion; solvent free; surface properties

(untitled) - Medina, J.; Salvadó, A.; del Pozo, A. (Int. J. Pharm., 2001)

(untitled) - Weiss, V. M.; Naolou, T.; Hause, G.; Kuntsche, J.; Kressler, J.; Mäder, K. (J. Controlled Release, 2012)

(untitled) - Lefebvre, G.; Riou, J.; Bastiat, G.; Roger, E.; Frombach, K.; Gimel, J.-C.; Saulnier, P.; Calvignac, B. (Int. J. Pharm., 2017)

(untitled) - Maupas, C.; Moulari, B.; Béduneau, A.; Lamprecht, A.; Pellequer, Y. (Int. J. Pharm., 2011)

(untitled) - Harun, S.; Amin Nordin, S.; Abd Gani, S. S.; Shamsuddin, A. F.; Basri, M.; Bin Basri, H. (Int. J. Nanomed., 2018)

(untitled) - Schädlich, A.; Hoffmann, S.; Mueller, T.; Caysa, H.; Rose, C.; Göpferich, A.; Li, J.; Kuntsche, J.; Mäder, K. (J. Controlled Release, 2012)

(untitled) - Hirsjärvi, S.; Sancey, L.; Dufort, S.; Belloche, C.; Vanpouille-Box, C.; Garcion, E.; Coll, J.-L.; Hindré, F.; Benoît, J.-P. (Int. J. Pharm., 2013)

(untitled) - Hirsjärvi, S.; Dufort, S.; Gravier, J.; Texier, I.; Yan, Q.; Bibette, J.; Sancey, L.; Josserand, V.; Passirani, C.; Benoît, J.-P.; Coll, J.-L. (Nanomedicine (N. Y., NY, U. S.), 2013)

(untitled) - Lainé, A.-L.; Gravier, J.; Henry, M.; Sancey, L.; Béjaud, J.; Pancani, E.; Wiber, M.; Texier, I.; Coll, J.-L.; Benoît, J.-P.; Passirani, C. (J. Controlled Release, 2014)

(untitled) - Heurtault, B.; Saulnier, P.; Pech, B.; Proust, J.-E.; Benoît, J.-P. (Pharm. Res., 2002)

(untitled) - Friberg, S. E.; Corkery, R. W.; Blute, I. A. (J. Chem. Eng. Data, 2011)

(untitled) - Heurtault, B.; Saulnier, P.; Pech, B.; Venier-Julienne, M.-C. C.; Proust, J.-E. E.; Phan-Tan-Luu, R.; Benoît, J.-P. (Eur. J. Pharm. Sci., 2003)

(untitled) - Roethlisberger, D.; Mahler, H.-C.; Altenburger, U.; Pappenberger, A. (J. Pharm. Sci., 2016)

(untitled) - Stranz, M.; Kastango, E. S. (Int. J. Pharm. Compd., 2002)

(untitled) - Viegas, T. X.; Henry, R. L. (Int. J. Pharm., 1998)

(untitled) - Gadelha, G.; Nawaz, M. S.; Hankins, N. P.; Khan, S. J.; Wang, R.; Tang, C. Y. (Desalination, 2014)

(untitled) - Cheuvront, S. N.; Kenefick, R. W.; Heavens, K. R.; Spitz, M. G. (J. Clin. Lab. Anal., 2014)